Fintech and its impact on Islamic fund management in Malaysia: a legal viewpoint - Miskam, Surianom; Yaacob, Abdul Monir; Rosman, Romzie (Emerald Publishing, 2019)
The global Islamic financial landscape is changing with rapid advances in technology. The increasingly tech-savvy demography is presenting both opportunities and challenges to the industry. With the advances in e-finance and mobile technologies, financial technology (Fintech) innovations emerged by combining the e-finance, Internet, social networking services, social media, artificial intelligence (AI) and big data analytics. Fintech promises to reshape the Islamic financial landscape by improving processes’ efficiencies, cost-effectiveness, increased distribution, Sharīʿah compliance and financial inclusion. As far as the Islamic fund management industry is concerned, AI seems to be the keyword. Islamic fund managers have recently started to incorporate AI and big data analytics into their strategy in the process of making accurate decisions based on facts and figures, which eliminates any biases and personal intuition. This disruption in status quo is raising new issues, new concerns and new exciting opportunities. While disruption may carry negative connotations the industry players have been embracing the innovation and potential revolution the technology could offer. Thus, the objective of this chapter is to discuss legal aspects of Fintech and its impact on the Islamic fund management industry in Malaysia. This chapter introduces a historical overview of Fintech and its evolution in the Islamic fund management industry. This chapter further provides an overview of the legal and regulatory aspects of Fintech with regards to the industry. Finally, legal issues and challenges are identified and discussed. Being a legal research, this chapter adopts a qualitative method by analysing the relevant literatures on the subject. This chapter is expected to provide an insight into the application of Fintech and its impact on the Islamic fund management industry in Malaysia.